Preliminary characterization and evaluation of local concrete sludges for use as supplementary cementitious materials - Ashfaque Ahmed Jhatial; Iveta Nováková; Eirik Gjerløw; Christian John Engelsen (Case Studies in Construction Materials)
Concrete sludge (CS) is an emerging supplementary cementitious material (SCMs). However, the diverse range of SCMs and their various sources for each necessitate initial characterization and evaluate the potential of CS as a SCM. In this study, CS were collected from seven different concrete producers (designated as CS1 to CS7) in the Northern Norway region. This preliminary characterization aims to provide valuable insights into the feasibility of using CS in cement or concrete production. It was determined that the chemical composition of CS was found to meet the EN 450–1 requirements, while most of the CS evaluated, exhibited hydraulic characteristics. The Rankin Classification of analyzed CS indicates a prevalent hydraulic nature, with most CS exhibiting CaO/SiO2 ratios greater than 2.0, thus suggesting potential for hydraulic applications. It was also observed that with 30 minutes of pulverizing, the particle size of the CS samples exhibited an average decrease ranging from 6.8 % to 78 %. This variation is likely due to differences in initial particle size and composition. Larger particles are generally more susceptible to breakdown during pulverization, which explains the higher reduction observed in some samples. Conversely, samples with higher coarse sand content and the resistance of specific aggregates to grinding exhibited the smallest reduction. These differences highlight the impact of material composition on the effectiveness of the pulverization process. An increase in the specific surface area and a decrease in the particle size of CS were observed after grinding, showing the potential for mechanical activation of CS as a potential SCM. However, prolonged pulverization beyond 30 minutes is not recommended, as only marginal improvement beyond 30 minutes of pulverization were observed. The XRD analysis revealed that the CS samples contained 2.29–28.47 %, with an average of 8.3 % amorphous content, reflecting the variation of cement paste in the CS. The findings suggest that CS can be categorized into two SCMs based on their operation: precast CS, characterized by siliceous and alkali-rich properties, and ready-mix CS, which is lime-rich and exhibits hydraulic properties, enabling tailored applications in cement and concrete production.